2013
DOI: 10.1007/s10901-013-9364-3
|View full text |Cite
|
Sign up to set email alerts
|

How housing outcomes vary between the Belgian regions

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer Science +Business Media Dordrecht. This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…The higher exposure of renters to air pollution confirms the studies of Lam and Chung (2012), Grineski et al (2007) and Chakraborty (2009). Contrasting Grineski et al’s results, adding the percentage of rental houses to the model also substantially reduced the effect of income in our models, which could be explained by the strong association between socioeconomic vulnerability and renting in Belgium (Winters & Heylen, 2014). However, the most important housing variable in our models appeared to by the number of house moves per 1000 inhabitants, both in the non-spatial and the spatial model explaining air pollution exposure.…”
Section: Discussionsupporting
confidence: 76%
“…The higher exposure of renters to air pollution confirms the studies of Lam and Chung (2012), Grineski et al (2007) and Chakraborty (2009). Contrasting Grineski et al’s results, adding the percentage of rental houses to the model also substantially reduced the effect of income in our models, which could be explained by the strong association between socioeconomic vulnerability and renting in Belgium (Winters & Heylen, 2014). However, the most important housing variable in our models appeared to by the number of house moves per 1000 inhabitants, both in the non-spatial and the spatial model explaining air pollution exposure.…”
Section: Discussionsupporting
confidence: 76%
“…The strong focus of the Belgian housing policies on encouraging owner-occupation is partly to blame. The regional governments mainly provide a favorable fiscal regime for home-buyers, while subsidies for renters remain quite low (Winters and Heylen, 2014). A study from Flanders, the Northern part of Belgium, showed that selling of the jointly owned house to a third party after separation has decreased over time-in the most recent studied separation cohort (2001-2010), 35% of men and 31% of women became sole homeowners, whereas 23% sold their house to a third party (Pasteels and Mortelmans, 2015).…”
Section: The Belgian Contextmentioning
confidence: 99%
“…In a country like Belgium, the question of who moves might be of the utmost importance. Belgium not only has high divorce rates (Eurostat, 2015a), it is also characterised by a limited supply of good quality and affordable (social and private) rental housing-the type of housing where many separated tend to end up (Winters and Heylen, 2014;Pittini et al, 2015;Mikolai and Kulu, 2017). We focus on the importance of partners' absolute and relative education because education is multifaceted: a higher level of education not only reflects better labour market opportunities and higher earnings potential (Kalmijn, 1998), it also contributes to partners' personal values, beliefs, skills and knowledge (or human capital) (Becker, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For the majority of relocations, moving to a specific area is not an important objective. In particular, only 7% of households that moved mentioned work as the main reason, while 69% indicated dissatisfaction with the current dwelling and 24% pointed at personal reasons (Winters and Heylen, 2013). Large differences in house prices, especially between Wallonia and Brussels, can be an obstacle for people to relocate over longer distances.…”
Section: High Homeownership Weighs On Residential Mobilitymentioning
confidence: 99%
“…Many people who would qualify for social housing based on their financial means have to resort to the private rental market, and the higher rents weigh heavily on their budgets. Affordability problems are most severe in Brussels, where the share of households with housing cost overburden is above 21%, compared to around 10% in Wallonia and 6% in Flanders (Winters and Heylen, 2013). The difference between the capital and the other Regions reflects both the higher cost of accommodation and the much higher share of the population at risk of poverty.…”
mentioning
confidence: 99%